PENGARUH KOMITE AUDIT TERHADAP HUBUNGAN ANTARA DISCRETIONARY ACCRUALS DAN CUMULATIVE ABNORMAL RETURN - ARYA PRADIPTA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
This study aims to investigate the influence of the audit committee on the relationship between discretionary accruals and cumulative abnormal return. Sample of the research are fifty companies that outlines the audit committee in 2005. The results showed that there was no relationship between discretionary accruals and cumulative abnormal return. Thus be seen that the management of fifty companies which include audit committee in 2005 did not try to give their private information through discretionary accruals. The audit committee does not affect the ability of discretionary accruals to convey private information.